Immunotherapeutic and oncolytic viral therapeutic strategies in pancreatic cancer. (May 2014) - Khan, Meaghan L; Halfdanarson, Thorvardur R; Borad, Mitesh J
ABSTRACT: : Pancreatic adenocarcinoma is an aggressive disease with dismal outcomes despite recent advances using combination chemotherapeutic regimens. The lack of an adequate immune response to malignant cells has been identified as a factor associated with tumor aggressiveness and refractoriness to systemic treatment. Preclinical and early clinical studies have identified numerous immunotherapeutic and oncolytic viral therapeutic strategies aimed towards amplifying the immune reaction to pancreatic cancer and have established encouraging results. Promising antitumor efficacy has been observed both in vitro and in vivo with many of these approaches. These novel applications have also led to improved understanding of the process of pancreatic tumor growth and invasion, knowledge of the tumor microenvironment and have pioneered further investigations of similar therapies. Here we review both immunotherapeutic and oncolytic viral therapeutic strategies in pancreatic cancer.